Technical and economical analyses of fuel cell to electrical operation in urban buses - Braga, Lúcia Bollini; Souza, Antonio Carlos Caetano de; Silveira, José Luz; Antunes, Julio Santana (Revista Ciências Exatas, 2009)
The global warming and the decrease of life quality of population caused mainly by burning of fossil fuels that emit millions of tons of pollutants to the environment. Besides, the certainty that those fossil fuels are non-renewable resources allows more researches in cleaner energy, and particularly in vehicles. This way, fuel cell has received particular attention because it can be applied in urban transport and improves the actual environmental situation of the world. The fuel cells appear like a promising technology for energy generation. Among several technologies in the present, the PEMFC (proton exchange membrane fuel cell) is the most appropriated and take part of prototypes of vehicles in progress, because it combines durability, high power density, high efficiency, good response at room temperatures and it works at relatively low temperatures, besides that it is easy to turn it on and off and it is able to support present vibration in vehicles. One part of this paper was developed in Stockholm, where there are some buses within the CUTE project that have been in operation since January 2004.